Assessment of the interrelationship between competitive confidence and cognitive skills among basketball players - Rogaleva, L.; Volpert, B.; Dosmanov, A.; Burkova, A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the relationship between indicators of competitive confidence and mental skills among students of different levels of athletic skill.